login
G.f. A(x) satisfies A(x) = 1 + x/A(x)^3 * (1 - A(x) + A(x)^4).
2

%I #23 Dec 13 2024 09:40:35

%S 1,1,0,3,-6,28,-105,444,-1897,8338,-37305,169471,-779537,3623500,

%T -16993990,80316081,-382136133,1828896726,-8798796709,42528048930,

%U -206413678447,1005623593109,-4916026689088,24106987842416,-118551374861525,584526569727010,-2888995759466360

%N G.f. A(x) satisfies A(x) = 1 + x/A(x)^3 * (1 - A(x) + A(x)^4).

%F a(n) = (1/n) * Sum_{k=0..n} (-1)^k * binomial(n,k) * binomial(n-4*k,n-k-1) for n > 0.

%o (PARI) a(n) = if(n==0, 1, sum(k=0, n, (-1)^k*binomial(n, k)*binomial(n-4*k, n-k-1))/n);

%Y Cf. A317133, A364759, A377458, A378958, A378920.

%Y Cf. A371890.

%K sign

%O 0,4

%A _Seiichi Manyama_, Dec 12 2024